Desinfecção de lodo de esgoto anaeróbio para fins agrícolas - Alves Filho, Amilton (2014)
This study aimed to evaluate the effect of combination of chemical treatments and solarization on cleaning and chemical and physical composition of sewage sludge a waste from sewage treatment system from an upflow anaerobic sludge blanket reactor and UASB (Upflow Anaerobic Sludge Blanket Reactor) of Treatment Plant - ETE Uberabinha located in Uberlândia-MG. It is known that the presence of pathogenic organisms and heavy metals are major limiting the use of this sludge in agriculture. For this, we used the split plots in time, in an experimental design of randomized blocks 5x3 + 1, with four replicates, in four (4) evaluation periods (0, 7, 14 and 21), and the zero time (0) corresponded to additional treatment, totaling 64 plots. The treatments consisted of pure sludge, sludge more peracetic acid (260 mg L-1), homogenized with hydrated lime sludge (CaOH2) in the proportion of 30% of the dry mass of sludge, sludge with sodium hypochlorite (2500 mg L-1) and more quaternary ammonium sludge (2400 mg L-1). Treatment with hydrated lime reduced levels of total and thermotolerant at 7 days after mixing with the sludge, meeting the requirements specified in environmental legislation for agricultural use coliforms. A solar radiation alone did not reduce the concentration of fecal coliforms to acceptable limits by environmental standard. Evaluated treatments did not cause temperature differences in the mass of sewage sludge limed sludge showed the highest levels of calcium (302 g kg-1), magnesium (4.2 g kg-1) and total solids, lower levels of Zn, Cu, Cd, Cr, Ni, volatile solids and moisture after mixing with sewage sludge. Concentrations of heavy metals (Zn, Cu, Cd, Cr, Ni and Pb) were below the limits specified in Resolution CONAMA n. 375/2006. The limed sludge showed the highest pH (12.65) lower levels of aluminum (20.10 g kg-1), phosphorus (1.6 g kg-1), organic matter (368, 6 g kg-1), carbon (213.80 g kg-1), nitrogen (20.88 g kg-1) and sodium (0.61 g kg-1). In treatment with sodium hypochlorite, sodium highest values (4.10 g kg-1) were recorded. The evaluation periods did not influence the concentration of nutrients and heavy metals. Considering Resolution CONAMA n. 375/2006, limed sludge in the ratio of 30% by weight of silt meets the parameters of fecal coliform, being more efficient. You can use the limed sludge in agriculture provided it meets the other requirements explicit in CONAMA Resolution n. 375/2006.